Ultrasonic studies on interionic interactions of some alkali metal halides in aqueous d-glucose solution at varying molalities and temperatures - Thirumaran, S; Job Sabu, K (Journal of Experimental Sciences, 2013)
The present experimental investigation was carried out in order to explore the possible molecular interionic interactions of alkali metal halides namely, sodium chloride, potassium chloride, potassium bromide and potassium iodide in aqueous D-glucose solution at 303.15, 308.15K and 313.15 K. Experimental values of density (ρ), viscosity (η) and ultrasonic velocities (U) were carried out on the liquid ternary mixtures of water +D-glucose + alkali metal halides The binary solvent mixture of water + D-glucose was prepared under molality(m) basis say, at two fixed molalities (0.2 and 0.4mol.kg-1). Alkali metal halides (NaCl, KCl, KBr and KI) were added under different molalities with these binary solvent mixtures. The related and relevant parameters correlated to our present study such as adiabatic compressibility (b), molal hydration number (nH), apparent molal compressibility (jk), apparent molal volume (jv), limiting apparent molal compressibility ( ), limiting apparent molal volume ( ) and their associated constants (SK, SV), partial transfer volume (âˆ† ) from water to aqueous solution were determined. In order to stress more on the viscometric data to substantiate its importance, the viscosity B-coefficient has been meticulously evaluated, The present investigation has exploited the possible molecular associations such as ion-ion, ion-solvent, solute-solvent, solute-solute etc., which are identified and eventually discussed about the behaviour of solutes (alkali metal halides) in the solvent mixture.